How to Improve Fine Motor Skill Learning in Dentistry. (8th February 2021) - El-Kishawi, Mohamed; Khalaf, Khaled; Winning, Tracey
Abstract : Introduction . Restorative dental treatment is a complex task involving various procedures which require the development and integration of both theoretical knowledge and fine motor skills. It aims to provide the theoretical background and role of key factors in learning these skills. Materials and Methods . The following electronic databases were searched to identify relevant articles to our topic: PubMed, Medline, Google Scholar, and Scopus. Generic keywords, that is, factors, fine, performance, and dentistry, and MeSH terms, that is, "learning, " "instruction, " "patient simulation, " "motor skills, " "perception, " "tactile, " "neurophysiology, " and "working memory" were used to conduct our comprehensive search. Results and Conclusions. Several techniques are used in performing different restorative procedures in dentistry, that is, root canal preparation, root planning, and minor oral surgery procedures. Mastering these techniques requires a good understanding of the underpinning cognitive, sensory, and neuromuscular processes. Factors including the amount and timing of instructions provided, cognitive abilities, and practice schedule of learning trials may have significant implications on the design of fine motor skill learning exercises.